1995
DOI: 10.1063/1.114348
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of band gaps in silicon nanostructures

Abstract: The size dependence of the energy band gap for hydrogen saturated silicon clusters, wires and slabs are calculated using all electron density functional theory. The hydrogen saturation is considered as a model for a wider band gap insulator enclosing the silicon structures. With this perspective in mind, an effective mass model with finite barriers for both valence and conduction band is found to semiquantatively account for the numerical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
177
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(204 citation statements)
references
References 19 publications
23
177
0
1
Order By: Relevance
“…29 The latter result is further supported by calculated mean sizes from theoretical correlations. 28 The PL decay times, , of species a were obtained from tri-exponential decay fittings of the PL traces detected at 450 nm upon 388 nm excitation (see in Table 1 These observations agree satisfactorily with reported cytotoxicity studies of SiNPs with surface attached amino groups. 33 Since in aqueous media of pH 7-8 both, PA-FeSiNPs and SiO x -Fe-SiNPs are positively charged, it is suggested that the nature of the charge, -NH 3 + vs Fe-OH 2 + is a contributing factor to the differential cell toxicity.…”
Section: Silicon Nanoaparticles Characterization: the Analysis Of Thesupporting
confidence: 72%
See 2 more Smart Citations
“…29 The latter result is further supported by calculated mean sizes from theoretical correlations. 28 The PL decay times, , of species a were obtained from tri-exponential decay fittings of the PL traces detected at 450 nm upon 388 nm excitation (see in Table 1 These observations agree satisfactorily with reported cytotoxicity studies of SiNPs with surface attached amino groups. 33 Since in aqueous media of pH 7-8 both, PA-FeSiNPs and SiO x -Fe-SiNPs are positively charged, it is suggested that the nature of the charge, -NH 3 + vs Fe-OH 2 + is a contributing factor to the differential cell toxicity.…”
Section: Silicon Nanoaparticles Characterization: the Analysis Of Thesupporting
confidence: 72%
“…28 exhibit more intense PL than larger ones. 29 The latter result is further supported by calculated mean sizes from theoretical correlations.…”
Section: Silicon Nanoaparticles Characterization: the Analysis Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Figures quoted for quantum efficiency are typically around 5%. 2 There are now a large number of groups working on many aspects of porous silicon, from fundamental theory [3][4][5] to the production of prototype luminescent devices. [6][7][8] However, the recognized instability of the material may suggest that it is perhaps less suitable for general device use than was originally thought.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been extensively demonstrated that in H-terminated SiNWs quantum confinement induces a gap-broadening effect [11,12,13], little is known about surface reconstruction of nonpassivated wires and about their electronic structure. Theoretical studies of the structure of the thinnest possible SiNW [14,15] have been previously published.…”
mentioning
confidence: 99%